Sex-related differences in patients with coronavirus disease 2019: results of the Cardio-COVID-Italy multicentre study. Issue 4 (31st January 2022) - Lombardi, Carlo Mario; Specchia, Claudia; Conforti, Fabio; Rovere, Maria Teresa La; Carubelli, Valentina; Agostoni, Piergiuseppe; Carugo, Stefano; Danzi, Gian Battista; Guazzi, Marco; Mortara, Andrea; Piepoli, Massimo; Porto, Italo; et al.
Abstract : Introduction: The role of sex compared to comorbidities and other prognostic variables in patients with coronavirus disease (COVID-19) is unclear. Methods: This is a retrospective observational study on patients with COVID-19 infection, referred to 13 cardiology units. The primary objective was to assess the difference in risk of death between the sexes. The secondary objective was to explore sex-based heterogeneity in the association between demographic, clinical and laboratory variables, and patients' risk of death. Results: Seven hundred and one patients were included: 214 (30.5%) women and 487 (69.5%) men. During a median follow-up of 15 days, deaths occurred in 39 (18.2%) women and 126 (25.9%) men. In a multivariable Cox regression model, men had a nonsignificantly higher risk of death vs. women ( P = 0.07). The risk of death was more than double in men with a low lymphocytes count as compared with men with a high lymphocytes count [overall survival hazard ratio (OS-HR) 2.56, 95% confidence interval (CI) 1.72–3.81]. In contrast, lymphocytes count was not related to death in women ( P = 0.03). Platelets count was associated with better outcome in men (OS-HR for increase of 50 × 10 3 units: 0.88 95% CI 0.78–1.00) but not in women. The strength of association between higher PaO2 /FiO2 ratio and lower risk of death was larger in women (OS-HR for increase of 50 mmHg/%: 0.72, 95% CI 0.59–0.89) vs. men (OS-HR: 0.88, 95% CI 0.80–0.98; P = 0.05). Conclusions: Patients' sex is a relevant variable that should be taken into account when evaluating risk of death from COVID-19. There is a sex-based heterogeneity in the association between baseline variables and patients' risk of death.